Evaluation of an automated light transmission aggregometry. (3rd October 2017) - Ling, Li-qin; Liao, Juan; Niu, Qian; Wang, Xia; Jia, Jin; Zuo, Cheng-hua; Jiang, Hong; Zhou, Jing
Abstract: Light transmission aggregometry (LTA) is the "gold standard" for platelet function assessment, but it is time-consuming and labor intensive. Recently, an automated platelet aggregation method has been developed on a routine coagulation analyzer (Sysmex CS-2100i). In this study, the performances of CS-2100i including repeatability, correlation with a reference aggregometer (Chrono-log Model 700), and the threshold limitation of platelet counts in platelet-rich plasma (PRP) were evaluated for clinical use. The agonists were adenosine diphosphate (ADP), arachidonic acid, collagen, epinephrine, and ristocetin. The platelet concentration of PRP was adjusted with platelet-poor plasma (PPP) and physiological saline (PS). The CS-2100i showed an excellent repeatability and a strong correlation with the Chrono-log 700 in performing platelet aggregation, and its threshold limitation of platelet counts in PRP was 80 × 10 9 /L. PPP had an inhibitory impact on platelet aggregation induced by ADP, arachidonic acid, collagen or epinephrine; while PS had an inhibitory impact on ristocetin-induced aggregation. PS should be used to adjust PRP for ADP-, arachidonic acid-, collagen-, or epinephrine-induced aggregation; while PPP was recommended for ristocetin-induced aggregation. The CS-2100i showed an excellent repeatability, a strong correlation with Chrono-log 700, a lower platelet count requirement, a shorter turnaround time for samples, the advantage of being a walk-away technology, and the ability to perform a highly standardized platelet function assessment.